How do you prove (sectheta - tantheta) (csctheta +1)=cottheta?

1 Answer
Jul 5, 2016

The following identities will be necessary for this problem:

sectheta = 1/costheta

csctheta = 1/sintheta

tantheta = sin theta/costheta

cottheta = costheta/sintheta

1 -sin^2theta = cos^2theta

Now, we have what we need to prove:

(1/costheta - sintheta/costheta)(1/sintheta + 1) = costheta/sintheta

((1 - sin theta)/costheta)((1 + sin theta)/sintheta) = costheta/sintheta

(1 - sin^2theta)/(costhetasintheta) = costheta/sintheta

cos^2theta/(costhetasintheta) = costheta/sintheta

costheta/sintheta = costheta/sintheta

Identity proved!!

Practice exercises:

Prove the following identities:

a) sintheta + cos^2theta/(1 + sin theta) = 1

b) sintheta(csctheta - sin theta) = cos^2theta

exercises taken from http://www.swrschools.org/assets/algebra_2_and_trig/chapter12.pdf

Hopefully this helps and good luck!